Reshaping knowledge management in the digital age through the integration of artificial intelligence and deep knowledge - Balbal, Hasnaoui; Bouchareb, Nasser (The International tax journal, 2025)
In the digital era, the transformation of vast, heterogeneous data into actionable knowledge stands as a pivotal challenge for organizations striving to maintain competitive and adaptive advantages. This paper explores how artificial intelligence (AI) serves as a catalyst for advancing knowledge management (KM), enabling the conversion of raw data into contextually rich, strategic insights. Traditional KM frameworks, designed for static and structured information, falter in the face of dynamic, unstructured data streams. By integrating AI technologies, organizations can automate data aggregation, enhance contextualization, and personalize knowledge dissemination. However, the adoption of AI-driven KM systems introduces ethical and operational challenges, including algorithmic bias, transparency deficits, and the need to balance autonomy with human oversight. The paper proposes interdisciplinary strategies to address these challenges, emphasizing ethical governance, participatory design, and hybrid human-AI collaboration. Ultimately, the study underscores that AI’s role in KM is not to replace human judgment but to augment it, fostering resilient, innovative ecosystems where data-driven insights align with organizational values and societal norms. The findings offer a roadmap for leveraging AI to anticipate challenges, optimize decision-making, and cultivate sustainable innovation in an increasingly complex digital area.